Prometeo y la naturaleza humana en el Humanismo Hispánico: la "Monarquía mística" de Lorenzo de Zamora - Nieto Ibáñez, Jesús María (2007)
Between the various interpretations of the myth of Prometheus in the western literature, the Monarquía mística of Lorenzo of Zamora is example of the wrong consideration on the woman and of the pessimism on the nature humanizes in the Christian Humanism.
Keywords: Zamora, Lorenzo de, -- m. 1614; Humanismo; Prometeo (Personaje mitológico)